How do the familiarity of a person and the type of training effect the behaviour of horses in the person test? - Boross, Barbara; Tóthné Maros, Katalin (Animal welfare, Ethology and Housing Systems (AWETH), 2008)
According to the present literature, individual differences, described as the temperament of the individual, could be measured with behavioural tests, such as open-field tests, person tests, handling tests or novel object test.The aim of this study was to observe the relationship between the human and horse, specifically to find parameters which describe the relationship between a horse and a familiar person in a standard situation. Additionally, the other objective of this experiment was to define how these parameters change in case of an unfamiliar test person. Previous researches demonstrate that horses generalize from the experience with a familiar person to interactions with unfamiliar persons (other trainers). Present experiments were carried out in 4 different places under similar conditions. The observation contained two types of tests: an open-field test (5 minutes) and a person test with 4 different phases: 1. voluntary animal approach test (180 sec); 2. test person invitation (120 sec); 3. the animal stays with the test person in one place (120 sec); 4. the horse follows the test person (180 sec). We recorded 37 horses with familiar test persons. Out of this 22 were tested with unfamiliar test persons, as well.Concerning our results horses were found to behave consistently over the 2 trials in their responses in the open-field test.Moreover, it was revealed that horses behaved similarly with the familiar and unfamiliar test person in the 2nd and the 3rd phase of the person test (invitation and stay). However, in the 1st and the 4th phase (voluntary animal approach, horse follow) animals had significantly better results with the familiar person than with the unfamiliar one. The last two phases are considered as the parameters that may describe the relationship between human and horse. These results were found to influence by other factors: 1. the number of persons training the horse; 2. the type of the training.
Keywords: open field test; person test; relationship; horse; familiar and unfamiliar person; training